Diagnóstico de hematuria enzoótica en bovinos del cantón Atahualpa mediante examen de orina con tiras reactivas - Feijoó Ordóñez, Héctor Santiago (2012)
This investigation realized it in the canton Atahualpa; from August 30 until November 22, 2011, with the purpose of diagnosing by means of examination of strips you reactivate the presence of hematuria enzoótica bovine in the above mentioned canton. The following aims appeared: 1. To diagnose hematuria enzoótica bovine by means of examination of strips you reactivate in ranching of the canton Atahualpa. 2. To determine the percentage of hematuria enzoótica bovine in agreement to the race, age and sex. To realize this thesis there was investigated a total of 500 animals of different ranching of the canton Atahualpa, in a space of 82 days. The realized studies determined that there is a high percentage of hematuria (25.6 %) present in the canton Atahualpa